Evaluate the impact of Shore Side Electricity on reducing exhaust emissions for ships, using the State Ship KN Masalembo - Dai Robbi, Shofa; Gunarti, Monika Retno; Yudiyanto, Prima Yudha; Gupron, Akhmad Kasan; Mulyanto, Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
Sea transportation accounts for 3% of the global greenhouse gas effect. The International Maritime Organization (IMO) is committed to reducing the impact of greenhouse gases by 50% in 2050—Indonesia is a maritime country with 10.8% of the world's ship register. High traffic has an impact on increased gas emissions. The IMO has made a policy on the Ship Energy Efficiency Management Plan. IMO recommends using Shore Side Electricity to reduce exhaust emissions, namely the use of electricity sources from land will reduce the operation of the ship's generator when berthing.This SSE case study uses the State Ship (KN) Masalembo at the Tanjung Perak Port. Evaluation of the impact of SSE on emission reduction is carried out by calculating electricity and fuel consumption. Based on fuel consumption, the amount of pollutants produced is known. A Descriptive quantitative method is used in this research. Based on the calculation, the electricity demand at 220 Volt voltage is 95,028 watts, and at 380 watts is 276,210 Watts. There are 3 generators on board with different output power. There are: auxiliary engine 1-2, harbour generator, and emergency generator. Each generator has different efficiency and fuel consumption. The Comparison of SSE reduction impact is largest in aux eng 1-2 worth 206,855.13 kg pollutant/ton of fuel. Fuel cost savings of up to 92.57% every year. SSE utilization is a solution for reducing exhaust emissions in the port area. Power generation using renewable energy sources is a recommendation for supporting SSE operations.